Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1021/es403199p
|View full text |Cite
|
Sign up to set email alerts
|

Novel Photo-Sulfite System: Toward Simultaneous Transformations of Inorganic and Organic Pollutants

Abstract: An efficient and green advanced oxidation process (i.e., photo-sulfite reaction) for the simultaneous oxidation of sulfite and organic pollutants in water is reported. The photo-sulfite system (UV-Fe(III)-sulfite) is based on the Fe-catalyzed sulfite oxidation and photochemistry of Fe(III) species. SO4(•-) and (•)OH radicals were identified in the photo-sulfite system with radical scavenging experiments using specific alcohols. This novel technology was consistently proven to be more favorable than the alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
64
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(65 citation statements)
references
References 44 publications
0
64
1
Order By: Relevance
“…Although SO4 − •-based advanced oxidation processes (S-AOPs) have drawn great attention in recent decades [22,24,25], little is known about the mechanism of As(III) oxidation by S-AOPs and the nature of the reactive oxygen species involved. The system using sulfite (generally expressed as S(IV)) as reactant and iron(II), iron(III), or light as inductor can also produce SO4 − • [26]. Recently, iron(II)/(III)-sulfite systems with or without UV light have been used to decolorize azo dyes, but dye mineralization in such systems is very poor [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Although SO4 − •-based advanced oxidation processes (S-AOPs) have drawn great attention in recent decades [22,24,25], little is known about the mechanism of As(III) oxidation by S-AOPs and the nature of the reactive oxygen species involved. The system using sulfite (generally expressed as S(IV)) as reactant and iron(II), iron(III), or light as inductor can also produce SO4 − • [26]. Recently, iron(II)/(III)-sulfite systems with or without UV light have been used to decolorize azo dyes, but dye mineralization in such systems is very poor [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Among these various AOPs, activated peroxymonosulfate (PMS) oxidation has been regarded as an interesting treatment method because PMS is more easily activated compared with hydrogen peroxide, which is one of the most commonly used oxidants in AOPs [7,8]. Although some research has demonstrated that heat and UV irradiation can be used to activate PMS to generate powerful radicals, these techniques are restricted in practical application owing to their high energy input [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The photo Fe(III)/sulfite system was also efficient at degrading bisphenol A around neutral pH [31]. Guo et al [29] demonstrated the effective degradation (90%) of 2,4,6-trichlorophenol within 180 min at pH 4 by the UV/Fe(III)/sulfite system. On the other hand, Fe(VI) alone is a powerful oxidant [32] and, in combination with sulfite, enhances the generation of oxidizing species.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Fe(II)-Fe(III)/sulfite systems are, therefore, good candidates for their use in the detoxification of contaminated water [22][23][24][25][26][27][28][29][30]32,34]. Fe(0) represents an alternative as an activator in radicals generation [35], and the use of Fe(VI) and sulfite produces a synergic effect, speeding up the removal of contaminants [28].…”
Section: Introductionmentioning
confidence: 99%